(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Augmented reality (VR) gaming is another sort of PC game which utilizes computer generated reality (VR) innovations that can give clients a totally practical, first-individual viewpoint of the game activity. Designing multiplayer virtual reality games is difficult because real-world influences can easily detract from immersion. In the 20th century, video games became the most important forms of entertainment. Its influence has multiplied and vastly enhanced in the twenty-first century. The gaming business was changed in such new market platforms with the introduction of mobile phones as well as portable devices. However, in order to establish virtual reality gaming as a credible new medium, it is necessary to provide enjoyable and social virtual reality experiences. This paper discuss design strategies for incorporating social interactions throughout game design while retaining immersion. The authors discuss the game design of such a collaborative regional multi-player/platforms virtual reality game as well as the effect of virtual reality on playing both from an enterprise as well as a player’s perspective in this article to illustrate how our methodologies may be used and how successful they are. Virtual reality technologies are fast gaining popularity across a wide range of sectors. Virtual reality is changing the way things are done in a range of sectors, from health to automotive, because there are great expectations for the future, particularly in the case of video games.